"Nivel de conocimiento en manipulación manual de carga y riesgo disergonomico en trabajadores de una cuorier de Trujillo" - Ñique Soto, Ana María del Pilar (2015)
Descriptive quantitative research conducted in a Courier Trujillo, Trujillo district, during the months of March - April 2015, in order to determine the relationship between the level of knowledge in Cargo Handling Manual and Risk in Disergonómico workers in a Courier. The sample consisted of 20 workers performing manual handling of load which was applied two instruments, the first related to the level of knowledge in Cargo Handling Manual and the second to measure disergonómico Risk (REBA). The results indicate that 55 percent of employees reached an average level of knowledge, the level of risk is 35 percent for the average value. The level of knowledge in Manual Handling of burden is a significant and positive relationship with the risk Disergonómico means that a greater lack of knowledge increases the risk disergonómico Manual load handling.